IMPLEMENTASI STRATEGI PEMBELAJARAN TERPADU DALAM MENINGKATKAN MOTIVASI BELAJAR ANAK PADA MASA PANDEMI COVID-19 DI SPS/RA BINTANG, LAMONGAN - Lestari, Indah Ayu; Nusantara, Widya (Jurusan Pendidikan Luar Sekolah Fakultas Ilmu Pendidikan UNESA, 2024)
The policies set by the government during the COVID-19 pandemic greatly affected early childhood education. The government's policy of requiring children to study from home resulted in a decrease in children's learning motivation. The right learning strategy to be implemented during a pandemic is an integrated learning strategy. Integrated learning activities from the whole involve the child's experience directly, with this the child will be more motivated to learn and be able to know the skills and potential they have. This study aims to describe the implementation and results of an integrated learning strategy in increasing learning motivation during the pandemic. This research uses qualitative research methods and descriptive research types. The research was conducted on 4 teachers who teach at SPS/RA Bintang. The research data were collected using semi-structured interviews, observation, and documentation methods which were carried out offline by visiting the SPS/RA Bintang institution directly. In this study, the data analysis technique used the theory of (Sugiyono, 2011) namely data reduction, data presentation, and data conclusion drawing. This study produces evidence that using an integrated learning strategy can increase children's learning motivation. Educators at SPS/RA Bintang have also made it clear that educators are also aware that children's learning motivation is very important in the learning process. Therefore, educators use integrated learning strategies as a solution to the problems they face during learning during the pandemic.